Comparative Study of Nitrogen Sources for Fertilisation ff Rainfed Bajra - Vyas, D L; Singh, S D; Daulay, H S; Misra, D K (Annals of Arid Zone, 2016)
In general, sources of nitrogen did not influence the grain and stalk yields. Differential response of crop to various sources of nitrogen in certain years then appears to be unrealistic. However, nitrogen treated plots indicated increase in yield over the control, but the three units of nitrogen gave yields of identical magnitudes. On the basis of the yield data pooled for all the seasons the optimum dose of nitrogen for locally improved variety R.S.K. worked out to be 23.2 kg/ha and at this level a yield of 397.15 kg and return of Rs 187.48 per ha can be predicted. Keeping in view the price per unit of manure/fertiliser, any source of nitrogen can be used for bajra cultivation under natural rainfall conditions of the sandy arid plains of Rajasthan.